Strategi Seorang Ibu Dalam Merawat Bayi Baru Lahir Di Tengah Pandemi Covid-19 (Studi Kasus Keluarga Ibu Alfiatul Maulidah Desa Grenden Puger Jember) - M.E, Rusmini; Hamdi M.E, Muhammad (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2023)
The COVID-19 pandemic has had an impact on society. Things that need to be considered include maintaining a safe distance (physical distancing), wearing masks, and washing hands frequently with soap and running water. Problems in newborns can be minimized by caring for newborns by a mother or her family, which cannot be separated from the role and support of health workers in improving the ability to care for babies. Newborns (BBL) are very susceptible to infections caused by exposure to viruses and germs during labor and shortly after birth. Inappropriate BBL care can cause health problems in infants and even death. The error was due to the lack of knowledge and low readiness of mothers about infant care, in addition to the activity of the Toddler Posyandu being temporarily postponed during the pandemic, information related to the growth and development of infants and toddlers was less than optimal. The results of activities regarding newborn care during this pandemic show satisfaction from the target families. Mothers who have newborns can understand and understand proper newborn care.